Light effects on seedling growth in simulated forest canopy gaps vary across species from different successional stages - Zhou, Lingyan; Thakur, Madhav P.; Jia, Zhen; Hong, Yu; Yang, Wenjie; An, Shuqing; Zhou, Xuhui (Frontiers in Forests and Global Change, 2023)
Tropical forests continue to suffer from various kinds of disturbances in the Anthropocene. An immediate impact of disturbances on forest ecosystems are the creation of numerous large and small canopy gaps, which dramatically affect forest structure and function. Yet, we know little about the effect of canopy gaps on forest successional trajectory. More specifically, the responses of seedlings from different successional stages to increased light intensity under large and small canopy gaps in understory remains unclear. In this study, dominant tree seedlings from early-, mid-, and late-successional stages were selected respectively from a tropical montane forest in Hainan Island, China to study their growth rate, biomass and traits. Our results showed that the light condition under small canopy gaps (SG, 10-15% of full sunlight) and large canopy gaps (LG, 40-50% of full sunlight) induced greater increment of relative growth rates for seedlings from early- and mid-successional stages relative to that in late- successional stage. Both SG and LG also significantly increased photosynthesis rate, leaf area (LA), light saturation point (LSP), root mass ratio (RMR) and root: shoot ratio, but decreased specific leaf area (SLA) of seedlings across successional stages. Tree seedlings from the early-successional stage displayed the greatest decrease in leaf mass ratio, increase in LA, LSP and RMR, in comparison to those from mid- and late- successional stages. Light condition and SLA were the most important factors for seedlings’ relative growth rate across successional stages. SLA connected the interaction between the light condition and successional stage on seedlings’ growth, thereby jointly explaining the 93% variation of seedlings’ growth, combining with area-based light saturated rate of CO2 assimilation. Our study highlights the distinct effect of disturbance-induced canopy gaps on seedling regeneration in the understory in tropical forest due to the variation of light intensity. We suspect that the seedlings from late-successional stage will recover relatively slow after disturbances causing canopy losses, which can have detrimental impacts on structure feature and successional trajectory in tropical forest, as well as forest-based ecosystem services.